PENGARUH MODEL PEMBELAJARAN LOGAN AVENUE PROBLEM SOLVING (LAPS)-HEURISTIC TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VIII SMP NEGERI 2 ONOLALU - Theresia Venty Fau, Yohanna; Smith Bago, Adam; Sarumaha, Murnihati; Solomasi Hulu, Liberkat (Jurnal Biogenerasi, 2025)
The purpose of this study was to determine the effect of the Logan Avenue Problem Solving-Heuristic learning model on student learning outcomes at SMP Negeri 2 Onolalu. The method used was a quasi-experimental method. The population of the study was all 54 students of class VIII of SMP Negeri 2 Onolalu. The sample of the study was class VIII-a as the experimental class and class VIII-b as the control class. The instrument used was a learning outcome test consisting of a pretest and posttest. Based on the hypothesis test, tcount = 2.0066 was obtained so that tcount> ttable, namely 7.6033> 2.0066. This shows that H0 is rejected and H1 is accepted. With the acceptance of H1, it is concluded that the Logan Avenue Problem Solving-Heuristic learning model has an effect on student learning outcomes. The researcher's suggestion is that science teachers, especially biology subject teachers, are expected to use the Logan Avenue Problem Solving-Heuristic learning model in learning because this learning model can explore and guide student knowledge oriented towards student participation in learning in the classroom.